Electrical Cable Identification Using Radio Frequency Identification (RFID) Technology - Mohamed Zaidi Ong, Muhammad Zaim; Ngajikin, Nor Hafizah (Evolution in Electrical and Electronic Engineering, 2021)
Widespread demand and consumption in the industry have led to rising copper prices. Because copper is very expensive, accessible, less secure, and relatively easy to steal and sell makes it a target for criminals. When a stolen cable is found, it is difficult for us to identify information on the stolen cable such as the location and organization that owns the stolen cable. Previously, the cable was tagged using the conventional plastic tag or wire marker. However, this type of marker is easy to be removed. Because of this issue, cable identification using RFID technology is proposed where the RFID tag will be attached to the electrical cable. With using this system, it can help to reduce the problem of locating the cable loss. The tags will be listed according to specific names. So, this project will help facilitate and save time and energy to locate the cable loss. Arduino UNO is selected as the microcontroller to program the system. The system is running using a 9v supply. The RFID PN5180 reader was used as a reader in this project, where it is equipped with unique features that improve performance, save energy and optimize power. The data that the RFID reader receives from the RFID tag will be processed by an Arduino microprocessor. When the data is processed, the LED and the buzzer will act simultaneously as indicators. The ID of the RFID tag will be shown on the OLED screen. As a consequence, the result shows that the system is able to run and the overall concept of the system can be implemented for the real application of the tracing system. The device can detect RFID tag up to 10cm through barriers such as iron and rubber. This tracking system can detect RFID tags through an iron barrier at a distance of not more than 6cm.